Accepting Reality as the Strategy of Maintaining a Marriage Reflected in Oscar Wilde's An Ideal Husband (1895): A Sociological Approach - NING TYAS, MARETA RAHAYU (2016)
ABSTRACT Marriage is a formal relationship between a man and a woman as husband and wife. There are many problems that will face for the marriage couple during the time they live together. Marriage is like the war castle. People, who are not married yet, want to marriage. In the other case, people who are in marriage want to divorce and feel uncomfortable with their marriage relationship. In this paper, the researcher puts some marital crisis, the strategies of maintaining a marriage, and the reason why the author gave concern in marital crisis of Victorian upper class society during 1890s time period. Finally, the researcher demonstrates that by accepting reality, people should maintain their marriage relationship and decide not to divorce. Keywords: marriage, marital crisis, strategy of maintaining a marriage